2020
DOI: 10.1016/j.annonc.2020.10.103
|View full text |Cite
|
Sign up to set email alerts
|

83MO AMG 510, a novel small molecule inhibitor of KRAS(G12C), for patients (pts) with advanced gastrointestinal (GI) cancers: Results from the CodeBreaK100 phase I trial

Abstract: Background: T-DXd is an antibody-drug conjugate composed of an anti-HER2 antibody and topoisomerase I inhibitor payload. Early studies have shown promising activity in advanced HER2-expressing tumors. DESTINY-CRC01 (NCT03384940) is a phase II, open-label, multicenter study of T-DXd in HER2-expressing mCRC. Methods: Patients (pts) with centrally confirmed HER2-expressing, RAS-wild type mCRC that progressed on ! 2 prior regimens received T-DXd 6.4 mg/kg every 3 weeks (q3w) in 3 cohorts (A: HER2 IHC 3+ or IHC 2+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At the time of the conduct of the SLR, 2 publications had reported the ORR in patients with KRAS G12C-positive mCRC and other gastrointestinal cancers and treated with sotorasib. 63 , 65 A phase I trial of sotorasib in 42 patients with CRC reported an overall ORR of 7.1% (95% CI: 1.5, 19.5) across all doses tested. 63 An ORR of 12.0% was reported for patients with CRC and other GI cancers treated with 960 mg/day of oral sotorasib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of the conduct of the SLR, 2 publications had reported the ORR in patients with KRAS G12C-positive mCRC and other gastrointestinal cancers and treated with sotorasib. 63 , 65 A phase I trial of sotorasib in 42 patients with CRC reported an overall ORR of 7.1% (95% CI: 1.5, 19.5) across all doses tested. 63 An ORR of 12.0% was reported for patients with CRC and other GI cancers treated with 960 mg/day of oral sotorasib.…”
Section: Resultsmentioning
confidence: 99%
“… 63 An ORR of 12.0% was reported for patients with CRC and other GI cancers treated with 960 mg/day of oral sotorasib. 65 However, this study lacked a comparator arm, precluding a comparison of outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that KRAS mutations may not be oncogenic driver alterations in chemotherapy resistant PDAC. This is supported by the lower rate of antitumor activity of KRAS G12C covalent inhibitors in KRAS G12C mutant PDAC compared with KRAS G12C mutant non-small cell lung cancer (48,49). There may also be other intracellular signalling pathways beyond FAK that interact with MEK and drive tumor growth in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase I CodeBreaK100 trial, KRAS G12C inhibitor sotorasib showed an ORR of 7.1% in various GI cancers ( n = 59) including one oesophageal cancer [ 99 ]. Another KRAS G12C inhibitor adagrasib was investigated in the KRYSTAL-1 multicohort phase I/II study and showed an ORR of 35% in the non-pancreatic GI cancers group.…”
Section: Tumour Agnostic Targetsmentioning
confidence: 99%